Status And Perception Of Elementary School Teachers In Relation To Inclusive Education: A Study In Barpeta District Of Assam - Anamika, Kalita (International Journal of Psychosocial Rehabilitation, 2020)
The Right to Free and Compulsory Education Act (RTE), 2009 mandates free and compulsory elementary education to all children including the Children with Special Needs (CWSN) (samgra.education.gov.in). As such now the all elementary schools welcome these children in the regular schools in a common classroom through inclusive education. In this regard an important element of inclusive education involves ensuring that all teachers are prepared to teach the CWSN effectively. Inclusion cannot be realized unless teachers are empowered with proper knowledge, skill, training, values and necessary attitudes to guide the CWSN to succeed. This paper intends to explore the perspective of elementary school teachers towards Children with Special Needs. 180 elementary school teachers were taken as sample and collected data using semi structured questionnaire. It was found that 61% teachers are not trained to teach CWSN and most of the teachers face academic and non academic challenges in dealing with them.